The Changing Japanese Economy and the Need for a Fundamental Shift in the Tax System - Noguchi, Yukio (American Economic Review, 1992)
Is a comprehensive income tax like the one envisioned by the Shoup Commission still the goal of the Japanese tax system? Or, have economic conditions changed so much that a different goal should be adopted? The gravest problem of the tax reforms of the 1980's was the absence of a judgment on this point. In fact, there was a contradiction with respect to choice of tax base. On the one hand, reform aimed at the comprehensive income tax goal by including in the tax base interest income and capital gains from sales of securities. On the other hand, there was a deviation from the principle in attempts to introduce a broadly based consumption tax. This is justified only if one admits the expenditure tax principle.